Culture and Quality Matter in Building Effective Mentorship Relationships with Native STEM Scholars. (3rd August 2022) - Estrada, Mica; Young, Gerald; Flores, Lilibeth; Hernandez, Paul R; Hosoda, K Kanoho; DeerInWater, Kathy
Abstract: Native peoples (Native American, Alaskan Native, Native Hawaiian) are underrepresented in academia; they represent 2% of the US population but 0.01% of enrolled undergraduate students. Native peoples share the experiences of colonization and forced assimilation, resulting in the loss of ancestral knowledge, language, and cultural identity. Recognizing history and the literature on social integration and mentorship, we followed 100 Native science and engineering scholars across a year of participation in the hybrid American Indian Science and Engineering Society mentorship program. The results showed that high-quality faculty mentorship predicted persistence a year later. Furthermore, mentors who shared knowledge of Native culture—through experience or shared heritage—uniquely contributed to the Native scholars' social integration and persistence through scientific community values in particular. Therefore, Native scholars may benefit from mentorship supporting the integration of their Native culture and discipline rather than assimilation into the dominant disciplinary culture.